DECONSTRUCTION AND RECONSTRUCTION OF THE KACU CONCEPT OF BATIK AS INSPIRATION FOR ARTWORKS - Ahda Yunia Sekar Fardhani (Fakultas Seni Rupa dan Desain ITB, 2021)
Batik is one of the arts that contains a whole descriptive belief about how Javanese interpret their lives. It is found inclassical batiks, which are still committed to the standard elements from Keraton as a center for preserving Javaneseculture. Through studying classical batik, the writer finds a concept of Kacu ratio used in making batik. For thewriter, the kacu is a local form of genius that belongs to the Javanese community. The consciousness of the emptinesspermeates all material forms that exist in the universe. This belief is also applied to the process of designing batikfabrics. For the Javanese, beauty lies in the balance of macro and microcosmos. The actual balance lies at the pointof paradox. Through this research, similarities in the numbers of the Kacu ratio, which is believed to be the goldenratio of the Javanese people in ancient times were sought. Then the equation would be applied to the artwork. Thisstudy uses a qualitative method with several literature sources to dissect the Kacu concept and apply it to works ofart. The writer uses the Kacu concept to arrange visual objects as a scale and balance composition through a formalistapproach. Finally, the writer presents batik and screen-printing techniques on textile. Therefore, the writer needsto study the Kacu ratio further to understand what this ancient ratio means in the beliefs of the Javanese people.